OBSERVATION OF COASTAL FRONT AND CIRCULATION IN THE NORTHEASTERN JAVA SEA, INDONESIA - Agus S. Atmadipoera; Edi Kusmanto; Adi Purwandana; I Wayan Nurjaya (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
The structure and spatial extent of a coastal front and circulation in the shallow (<55 m depth) northeastern Java Sea in Indonesia was investigated with a new dataset of high-resolution conductivity-temperature-depth (CTD) and along-track shipboard acoustic Doppler current profiler (SADCP) during a DIKTI-LIPI 2010 joint research cruise on R.V. Baruna Jaya 8.  The coastal front separates fresh warm coastal water derived mainly from Barito River discharge and the saline, cool Java Sea water.  The surface fresh water plume extends approximately 760 km from the Barito River estuary to the south, and its thickness varies from the surface to 10 m and 20 m depth, depending on its proximity to the fresh water source.  The front is aligned a northeast and east direction, probably related to a meandering of strong northeastward monsoon current in the eastern part of the Java Sea during the observation time. Keywords: hydrographic measurement, coastal front, Matasiri Islands, Barito River, the northwest monsoon current